2020
DOI: 10.1108/rpj-08-2018-0217
|View full text |Cite
|
Sign up to set email alerts
|

3D printing in tissue engineering: a state of the art review of technologies and biomaterials

Abstract: Purpose In the past decade, three-dimensional (3D) printing has gained attention in areas such as medicine, engineering, manufacturing art and most recently in education. In biomedical, the development of a wide range of biomaterials has catalysed the considerable role of 3D printing (3DP), where it functions as synthetic frameworks in the form of scaffolds, constructs or matrices. The purpose of this paper is to present the state-of-the-art literature coverage of 3DP applications in tissue engineering (such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(30 citation statements)
references
References 199 publications
(141 reference statements)
0
30
0
Order By: Relevance
“…As such, wound contraction remains a major issue in scaffold-driven dermal regeneration, and the prevention of scar formation has yet to be achieved. 3D printing has recently emerged as a potential method of addressing these challenges as it allows for the development of high-definition scaffolds with controlled mechanical and structural properties, for improved cell and tissue integration, to enhance skin regeneration [ 17 , 18 ]. Furthermore, the rate of production possible with 3D printing allows for more rapid and efficient treatments [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…As such, wound contraction remains a major issue in scaffold-driven dermal regeneration, and the prevention of scar formation has yet to be achieved. 3D printing has recently emerged as a potential method of addressing these challenges as it allows for the development of high-definition scaffolds with controlled mechanical and structural properties, for improved cell and tissue integration, to enhance skin regeneration [ 17 , 18 ]. Furthermore, the rate of production possible with 3D printing allows for more rapid and efficient treatments [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, fused deposition modeling (FDM) should be practiced to print composite like bioinspired materials as that is the quickest form of 3D printing, with proper printing parameters like nozzle size and nozzle temperature taken into account (Ko et al, 2019). To add more, there exists a wide gap between the industry and the research in order to develop a fine-tune method and biomaterial optimization if we talk about 3D printing as the best possible technique to provide benefit to the different industrial sectors like energy, medicine, automotive, environment, and military (Poomathi et al, 2020). However, during recent times, it has been observed that the fabrication of biomaterials is also possible by utilizing all the rapid prototyping techniques like 3D printing, mineralization, freeze-casting, laser engraving, and coating-assembly.…”
Section: Rapid Prototyping Of Biomimetic Designsmentioning
confidence: 99%
“…The spatial location of the cells in a 3D environment can be achieved to a great extent by manufacturing techniques like 3D bioprinting, 4D printing and others. [ 32,33 ] However, the understanding or modulating the dynamics of the cell signaling pathways for engineering a tissue (cell‐to‐cell interaction and cell‐to‐ECM interaction) requires a noncontact method like optogenetics. [ 34 ] The behavior of these engineered cells is modulated through noncontact mode optogenetic techniques which have a great spatiotemporal resolution; in comparison to its any chemical counterpart.…”
Section: Biocyber Physical Systemsmentioning
confidence: 99%
“…[ 129 ] Further advancements in the additive manufacturing have led to the design of scaffold mimicking the microarchitecture of the tissue scaffold. [ 32 ] The presence of poly(lactic‐ co ‐glycolic acid) microspheres tethered on the scaffold in addition with peptides can bring biomimetic microenvironment for cells seeded on these scaffolds. [ 130 ] The surface of the materials can be tailored to generate micro/nanotopologies that can provide contact guidance to the growing cells.…”
Section: Smart Biomaterialsmentioning
confidence: 99%